Pengaruh Aroma Terapi Minyak Essesial Jeruk Lemon Terhadap Penurunan Hiperemis Gravidarum Trimester I - Dewi Ciselia; Miftah Apriani (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Background: Pregnancy is a moment eagerly awaited by all women in their life phase. Starting from the moment of labor until the baby is born, this process begins. Pregnancy is a physiological process that occurs in women that begins from the first day of the last menstruation and lasts for 280 days, or 40 weeks, or 9 months 7 days. Objective: To determine the Effect of Aroma Therapy Lemon Essential Oil on Reducing Hyperemia Gravidarum Trimester I in pmb Erna Fitria Dewi Betung Banyuasin. Method: This method uses a Quasi Experimental method with a One Group Pre Post Design. That is, it involves pretest and posttest treatment groups. The instrument used is a direct interview method. The population of this study was 62 first trimester pregnant women who experienced emesis gravidarum. The first trimester of the study was conducted through sampling. Sampling is the process of selecting a portion of the population that can represent the existing population. The total sample size was 30 people. So that the minimum number of samples in the study was 15 people for each treatment group. This study will be conducted in September 2025, this study will be conducted at PMB Erna Fitria Dewi Results: Statistically, the p-value was obtained = 0.010 or less than the ? value (0.05). Based on the statistical results, it can be concluded that there is a difference between the frequency of nausea and vomiting between the control group and the intervention group. Conclusion: Giving Lemon Essential aromatherapy has been proven to be effective in reducing the frequency of emesis gravidarum in pregnant women with test results of 0.000